Design of Hybrid Smokeless Waste Burners Machine for Producing Organic Fertilizer - Riyadi, Sugeng; Setaji, Yogi; Pamekas, Hansyah Faisal; Setiawan, Reza (University of Muhammadiyah Malang, 2019)
The number of waste problems in Karawang are increasing but the handling is still limited. Every day, the Karawang community produces 920 tons of garbage. Of that amount, 400 tons of waste is sent to TPSA in Jalupang, while 520 tons of the remaining garbage is scattered everywhere. Overcoming the waste problem, it is necessary to have an environmentally friendly tool for direct burning of waste that can?t be recycled again. Hybrid Smokeless Waste Burners Machine (HSWBM) is an environmentally friendly technology by burning smokeless waste through smoke filtering using water or water scrubbers and using Hybrid technology by using electricity independently from solar panels and PLN electricity which is only used when weather conditions don?t. The method used is the design of tools, and component assembly. HSWBM has an environmentally friendly advantage because it uses smoke filtration through water and dangerous gas filtration so that the discharged gas is more environmentally friendly, electricity is independent of solar panels thus saving the operational costs of the tool. The remaining combustion or ash can be used as organic fertilizer or briquettes. Deposition of smoke in water (aerosols) for a mixture of fertilizing agricultural crops and reducing waste in Karawang so that a clean environment is created. The application of the use of this tool on a limited scale such as in schools, campuses and housing in Karawang.